LOCAL WISDOM-BASED HOME INDUSTRY DEVELOPMENT STRATEGY ISLAMIC ECONOMIC REVIEW (CASE STUDY OF PALM SUGAR IN KANDANGAN VILLAGE, LAUT TADOR DISTRICT, BATU-BARA REGENCY) - Yunara, Yulia; Batubara, Chuzaimah; Nasution, Muhammad Latief Ilhamy (LPPM Universitas Trunojoyo Madura, 2025)
The purpose of this research is to analyze the development strategy of sugar palm home industries based on local wisdom from the perspective of Islamic economics in Kandangan Village, Laut Tador District, Batu-Bara Regency. The background of the issue raised is the challenges faced by sugar palm home industries in optimizing local wisdom potential and integrating Islamic economic values to achieve business sustainability in the era of modernization. The novelty of this research lies in the implementation of a holistic development model that integrates SOAR analysis with local wisdom values and Islamic economic principles into a single strategic framework that has not been done before, especially in the context of sugar palm home industries in North Sumatra. This research uses qualitative methods with SOAR (Strengths, Opportunities, Aspirations, Results) analysis. It is suggested that the importance of harmonizing local wisdom and Islamic economic values in the development of home industries, as well as the need for an integrated strategy that includes promotion of eco-friendly products, digital marketing training, and the utilization of digital platforms to expand the market reach of palm sugar from Kandangan Village.Keywords: Strategy, SOAR, Home Industry, Local Wisdom, Islamic Economy, Palm Sugar